Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1109/jlt.2009.2015587
|View full text |Cite
|
Sign up to set email alerts
|

A 2.4-GHz Wireless-Over-Fibre System Using Photonic Active Integrated Antennas (PhAIAs) and Lossless Matching Circuits

Abstract: Abstract-This paper demonstrates that very low cost wirelessover-fibre systems can be implemented without RF amplification by using lossless matching techniques. Single stub matching circuits were designed on low loss substrates and integrated with photodiode chips and results show that the link gain can be theoretically improved by more than 8 dB. A 2-port link gain model is developed using Agilent ADS which allows simple wideband modeling of such systems. Finally the system is tested using a "live" access po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…This approach is being explored at lower frequencies and is termed as photonic active integrated antenna [27], [28]. The advantage in this case is that in the mm-wave bands antennas become sufficiently small such that they could be integrated directly on the same semiconductor substrate as the laser.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is being explored at lower frequencies and is termed as photonic active integrated antenna [27], [28]. The advantage in this case is that in the mm-wave bands antennas become sufficiently small such that they could be integrated directly on the same semiconductor substrate as the laser.…”
Section: Introductionmentioning
confidence: 99%
“…The key feature of a PhAIA‐based system is the ability to achieve relatively wideband conjugate matching between the photonic device and the antenna with no, or at least very simple, matching networks. This results in maximum power transfer and can result in significant improvement in link gain over a narrow bandwidth [ 8, 9]. To achieve conjugate matching, it is required to have a detailed knowledge of the input impedance of the photonic device.…”
Section: Input Impedance and Mll‐antenna Integration/mounting Confmentioning
confidence: 99%
“…A number of authors [10, 11] have reported the use of impedance‐matching networks for MLLs to improve RF injection efficiency; however, no one has reported the actual input impedances for these sections. The technique used here is called de‐embedding [8, 9, 12]. The term refers to the ability of a vector network analyzer (VNA), used to measure the impedance, to move its reference plane, such that the phase shift introduced by connectors and microstrip transmission lines can be removed.…”
Section: Input Impedance and Mll‐antenna Integration/mounting Confmentioning
confidence: 99%
See 2 more Smart Citations